Peran Guru PAI Dalam Pencegahan Pergaulan Bebas di SMPN 1 Biru-Biru Kabupaten Deli Serdang - Afrida Jayanti Sipahutar; Enny Nazrah Pulungan (LPPM Institut Nasional Laa Roiba Bogor, 2024)
The aim of this research is to prevent promiscuity through the role of Islamic Religious Education teachers by forming the character of Muslim students who are devout and have noble morals. This study uses a qualitative approach using observation data triangulation, interviews and documentation. The method used in this study is a qualitative method with a phenomenological approach. The research location was carried out at SMP N 1 Biru-Biru, Deli Serdang Regency. The process was carried out for 3 months starting from 10 April – 10 June 2023. There were two data sources used, namely primary and secondary sources. The condition of promiscuity is caused by many influencing factors including internal and external factors. The promiscuity that exists at SMP N 1 Biru-biru includes dating between students and also the rise of pornographic and romantic displays at school. The PAI teacher's role as a teacher in teaching promiscuity and adultery material is good, in the sense that he has prepared a) planning in the form of preparing lesson plans for theme 8 (avoiding promiscuity and adultery) b) choosing methods and media for promiscuity and adultery material in learning; c) demonstrating teaching materials; d) prepare learning evaluations and conduct material assessments of promiscuity and adultery. Then, as an educator, namely a) instilling the values of Islamic sex education in Qur'an recital activities and youth recitations, and getting used to implementing Islamic sex education (separating seats during social gatherings or school events, dressing to cover one's private parts, and asking for permission); b) Activate religious culture in schools with supervision and monitoring; c) Assistance in Spiritual activities; d) Conducting guidance to students with problems; e) Become a role model in avoiding promiscuity and adultery by maintaining Islamic social ethics. As for the obstacles of PAI teachers in preventing promiscuity, there is a lack of cooperation between teachers and people. Keywords: The Role of PAI Teachers, Prevention of Free Association, Juvenile Delinquenc